New European IT R&D policy : setting up the information society. - BANGEMANN, Martin (1995)
Claims that the world is at the beginning of the transition to a new information society and industry and the new R&D programme on information technology contributes to the realization of this society. Discusses the philosophy and content of the programme which is designed to improve the competitiveness of industry and of employment in the European Union by helping to provide the technologies needed to build the information infrastructure.